Media Gambar Berseri Berorientasi Problem Based Learning pada Materi Bahasa Indonesia Kelas IV Sekolah Dasar - Putu Ayu Lestari; MG Rini Kristiantari (Universitas Pendidikan Ganesha, 2022)
The pandemic period has a significant impact on the learning process, especially in elementary school. As a result, the delivery of learning materials becomes less effective, due to limited communication. The purpose of this study is to describe the design and find out the validity of the serialized image media oriented to problem base learning on the Indonesian elementary school. This type of research is development research. The subjects in this study consisted of learning material content experts, learning design experts, and 9 elementary school fourth grade students. The media in this study was developed using the ADDIE model. The method used in the collection of research data is using questionnaires, data analysis techniques using quantitative descriptive analysis. Based on the results of the study, 93.75% of the learning content expert test results were obtained with excellent qualifications, 95% learning design expert trials with excellent qualifications, 95% learning media expert trials with excellent qualifications, individual trials of 94.16% with excellent qualifications, and small group trials of 94.44% with excellent qualifications. Based on the results of expert tests on research that it can be concluded that problem-based learning-based serialized image media is suitable for use in learning activities, especially in the content of Indonesian lessons grade IV in elementary schools.